Changes in inflammatory mediators as a result of intermittent hypoxia in obstructive sleep apnea syndrome - Sozer, Volkan; Kutnu, Muge; Atahan, Ersan; Ozturk, Buket Caliskaner; Hysi, Ergi; Cabuk, Cansu; Musellim, Benan; Simsek, Gonul; Uzun, Hafize (WILEY, 2018)
BackgroundInflammation plays an important role in obstructive sleep apnea syndrome (OSAS). The objective of this study was to investigate the relationship of serum C-reactive protein (CRP), pentraxin-3 (PTX-3), procalcitonin (ProCT), interleukin-33 (IL-33) and its soluble receptor ST2 (sST2) with the syndrome severity and to show theirs importance as biomarkers. MethodsThis study comprises a total of 84 identical (sex and age wise) cases. Full-night polysomnography was performed in each patient. OSAS diagnosis and severity index being based on the widely used criterion known as Apnea Hypopnea Index(AHI). Subgroups were as follows: 24(AHI 30). ResultsPTX-3, IL-33 and sST2 receptors were significantly higher in OSAS groups than the control group (P<.001). However, both CRP and ProCT levels were similar in all subjects. There was a positive correlation between PTX-3 and BMI (r=0.446; P<.01), ODI (r=0.555; P<.01), IL-33 (r=0.348; P=.001) and sST2 (r=326; P=.002), while there was a negative correlation with minimum SaO(2) (r=-0.672; P<.01) in patient group. PTX-3 as a predictor of OSAS showed highest specificity (%91.7) and sensitivity (%91.7) (P<.001). ConclusionsPTX-3 can be a new indicator reflecting the inflammatory state in patients with OSAS. Since patients with OSAS could have more hypoxic state during sleep, we found higher PTX-3 level in those patients and a negative correlation between PTX-3 and minimum SaO(2), which could explain that PTX-3 levels can increase with the severity of disease. Our results suggest that PTX-3 as an inflammatory biomarker may play a crucial role as an indicator of syndrome severity in OSAS.
Keywords: interleukin-33; inflammation; intermittent hypoxia; obstructive sleep apnea syndrome; procalcitonin; pentraxin-3; C-REACTIVE PROTEIN; SYSTEMIC INFLAMMATION; ASSOCIATION; MARKERS; EVENTS; RISK; Respiratory System